2018
DOI: 10.1186/s13072-018-0192-2
|View full text |Cite
|
Sign up to set email alerts
|

Intrauterine hyperglycemia exposure results in intergenerational inheritance via DNA methylation reprogramming on F1 PGCs

Abstract: BackgroundThe existing reports about intergenerational or transgenerational effects of intrauterine hyperglycemia have included both intrauterine and postnatal metabolic exposure factors, while the impact of intrauterine hyperglycemia per se has not been assessed alone. A number of studies suggest DNA methylation reprogramming of gametes plays a crucial role in the metabolic inheritance, but it is unclear when and how DNA methylation patterns are altered when exposed to intrauterine hyperglycemia. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 41 publications
0
30
0
Order By: Relevance
“…In our previous study, we found that impaired glucose tolerance (IGT) in male offspring was more obvious than females, with parental characteristics and sex-speci c transmission [4]. Our further study showed that the aberrant DNA methylation reprogramming occurs as early as day 13.5 in primordial germ cells (PGCs) of the rst lial generation (F1), suggesting that intrauterine exposure alone is su cient to cause the epigenetic changes in the second lial generation (F2) [5].…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…In our previous study, we found that impaired glucose tolerance (IGT) in male offspring was more obvious than females, with parental characteristics and sex-speci c transmission [4]. Our further study showed that the aberrant DNA methylation reprogramming occurs as early as day 13.5 in primordial germ cells (PGCs) of the rst lial generation (F1), suggesting that intrauterine exposure alone is su cient to cause the epigenetic changes in the second lial generation (F2) [5].…”
Section: Introductionmentioning
confidence: 82%
“…Dysregulation of imprinted genes is a plausible mechanism linking maternal stressors with fetal growth [42]. For mechanism of transmission to F2 offspring, based on our previous research that intrauterine exposure alone is su cient to cause the epigenetic inheritance in F2 offspring [4,5], we mainly investigated the methylation status of F1 sperm, nding 56 genes down-regulated in F2-GDM hippocampus hypermethylated in F1-GDM sperm. Our result con rmed that the epigenetic memory carried by DNA methylation pattern could be reprogrammed in F1 germcell during fetal development in uterus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In utero exposure to a high-fat diet induces paternal obesity and insulin resistance accompanied by changes in sperm micro RNA content and germ cell methylation in two generations of offspring [149]. Intrauterine hyperglycemia exposure contributes to intergenerational metabolic changes in the F2 but not the F3 generation [150].…”
Section: Environmentally Induced Epigenetic Mutationsmentioning
confidence: 99%
“…Primordial germ cells ICR mice Obesity and insulin resistance [150] Paternal diet restriction significantly changed the DNA methyltransferase, Dnmt1 and the transcript of methyl CpG binding protein 2 (Mecp2) in F1, not in F2 and F3 generations. An increase in the expression of histone modification gene, histone deacetylase 1 (Hdac1) in fetus liver was found in F1 and F2.…”
Section: Intrauterine Hyperglycemiamentioning
confidence: 99%